The use of the Internet to activate latent ties in scholarly communities - Genoni, Paul; Merrick, Helen; Willson, Michele (First Monday Editorial Group, 2005)
This paper presents the results of a survey on the use of theInternet by university-based scholars to contact unknown peers. Thesecontacts are considered as examples of the activation of "latentties" which are said to exist within communities with associatedinterests. The research indicates that the Internet facilitates theactivation of these ties and that the degree to which it is used forthis purpose is associated with academic rank.